(untitled) (Western European Journal of Historical Events and Social Science, 2024)
This article explores the scientific and technical revolution in Uzbekistan, focusing on the transformative developments in science, technology, and innovation. It examines the historical context, current advancements, and future prospects. The study employs a comprehensive literature review, qualitative and quantitative analysis, and case studies to assess the impact of these changes on the nation’s socio-economic landscape.